Microstructure and mechanical properties of a high Nb-TiAl alloy fabricated by electron beam melting. (15th December 2018) - Kan, W.; Chen, B.; Jin, C.; Peng, H.; Lin, J.
Abstract: Electron beam melting (EBM) has been applied to fabricate a high Nb-TiAl alloy with a fully dense microstructure and good tensile properties at both room and high temperatures. The effects of preheating and melting parameters on melting, solidification, phase transformation and resulting microstructure formation in as-EBM high Nb-TiAl alloy were investigated by performing a design-of-experiments. Results show that the limited EBM processing window can be broadened to produce different characteristic microstructures ranging from nearly fully lamellar γ/α2 to equiaxed γ grains. Such a broadened processing window has been achieved by using stronger preheating beam current. A numerical simulation was performed to understand temperature evolution at a fixed point of interest where electron beam passed several times with a certain line offset within one build layer. Both the preheating and melting stages were considered in the model. Modelling results show that a higher preheating beam current resulted in a longer hold time within the temperature range between 1300 and 1380 °C (i.e. single α-phase region). This helped to produce fine lamellar microstructure in the high Nb-TiAl alloy. Fundamental principles are thus proposed in terms of controlling microstructure formation and fabricating fully dense high Nb-TiAl alloy in as-EBM condition. Graphical abstract: Highlights: A fundamental principle is proposed to control the microstructure of Nb-TiAl alloy in EBM with competitive tensile properties.